Ross Macdonald - Schopen, Bernard (Boston : Twayne Publishers, 1990)
Critical study of Macdonald's detective novels, examining his technique, themes, and providing an overview of the American detective novel.
Includes bibliographical references.
Young Adult.
Young Adult
Keywords: Macdonald, Ross, -- 1915-1983 -- Criticism and interpretation; Macdonald, Ross, -- 1915-1983.; Detective and mystery stories, American -- History and criticism